Influence of acetate- vs. lactate-containing fluid bolus therapy on acid-base status, electrolytes, and plasma lactate in dogs - Klein-Richers, Ute; Heitland, Annika; Hartmann, Katrin; Dörfelt, René (Frontiers in Veterinary Science, 2022)
Objective: Acetate- and lactate-containing fluids influence the acid-base and electrolyte status. This prospective, randomized, clinical study compared two balanced crystalloid solutions regarding their influence on acid-base status, electrolytes, and lactate values, when given to dogs as a resuscitation bolus of 30 ml/kg. Material and Methods: One hundred client-owned dogs presenting to the emergency service with signs of fluid deficits were randomly assigned to receive an intravenous bolus of 30 mL/kg of either a lactate- (LAC), or an acetate-containing solution (ACET). Before and after the bolus, vital parameters were assessed, and a venous blood gas analysis was performed. Results: Both solutions performed equally well in decreasing the heart rate (ACET: -10 ± 27 bpm, LAC: -12 ± 30 bpm; p = 0.737). The acetate-containing solution caused a significant decrease in plasma lactate levels (p = 0.016), anion gap (p < 0.001), and potassium (p < 0.001), and a significant increase in chloride (p < 0.001), and ionized calcium (p = 0.014). The lactate-containing solution caused a significant decrease in anion gap (p < 0.001), sodium (p = 0.016), and potassium (p = 0.001), and a significant increase in chloride (p < 0.001). ACET causes a stronger decrease in plasma lactate (p = 0.015), sodium (p = 0.039), potassium (p = 0.006), and an increase in chloride (p < 0.001), and ionized calcium (p = 0.016) compared to LAC. Conclusion: Both solutions caused mild changes in electrolyte concentrations and had minor influence on acid-base status when used for bolus therapy in dogs with fluid deficits. Further studies are needed to evaluate their influence on acid-base status, lactate, and electrolytes when used in larger volumes and for a longer time span.